Migrating Linux to Microsoft Azure - Skaria, Rithin; Willberg, Toni (Packt Publishing, 2021)
Learn to move on-premises virtual machines running on Linux servers to Azure with expert guidance, best practices, and optimized cost Key Features Work with real-life migrations to understand the do's and don'ts of the process Deploy a new Linux virtual machine and carry out automation and configuration management Learn debugging your system and collecting error logs with hands-on examples Book Description With cloud adoption at the core of digital transformation for organizations, there has been a lot of demand to deploy and host enterprise business workloads in the cloud. Migrating Linux to Microsoft Azure offers a series of actionable insights into deploying Linux workload to Azure. You will begin by learning about the history of IT, operating systems, Unix, Linux, and Windows, before moving on to look at the cloud and what things were like before virtualization. This will enable those not very familiar with Linux to learn the terms required to grasp the upcoming chapters. Furthermore, you will explore popular Linux distributions including RHEL 7, RHEL 8, SLES, Ubuntu pro, CentOS 7, and more. As you progress, you will dive into the technical details of Linux workloads such as LAMP, Java, and SAP. You will learn how to assess your current environment and plan migrating to Azure through cloud governance and operations planning. Finally, you will go through the execution of a real migration project and learn how to analyze, debug, and recover some common problems Linux on Azure users have encountered. By the end of this Linux book, you will be proficient in performing an effective migration of Linux workloads to Azure for your organization. What you will learn Explore the terminology and technology of various Linux distributions Understand the technical support co-operation between Microsoft and commercial Linux vendors Assess current workloads by using Azure Migrate Plan cloud governance and operations Execute a real-world migration project Manage project, staffing, and customer engagement Who this book is for This book is intended to benefit cloud architects, cloud solution providers, and any stakeholders dealing with migration of Linux workload to Azure. Basic familiarity with Microsoft Azure would be a plus.